Study of the structural anomaly of liquid water using upconverting thermometry of Brownian nanocrystals - Maturi, Fernando Eduardo [UNESP] (2024)
Although water is the most commonly used liquid, it is one of the most intriguing substances on planet Earth. This is because, despite having a simple chemical composition and molecular structure, liquid water exhibits an extraordinarily complex behavior when subjected to variations in temperature and pressure, setting it apart from other commonly used liquids. These anomalies in the behavior of water are easily observed under supercooling conditions, where water is cooled to temperatures below its freezing point, remaining in the liquid phase, thus revealing the existence of two distinct liquid states. While considered a remarkable explanation for the occurrence of its anomalous properties, the coexistence of these two liquid states of water is difficult to prove under normal conditions of temperature and pressure. This requires the development of new experimental approaches to investigate the peculiar characteristics of water that make life as we know it possible on our planet. Since the transition between the structures of the two liquid states of water occurs at a local level, the use of techniques capable of observing fluctuations in microscopic events is required. Therefore, this doctoral research work employs the technique of luminescence thermometry as a powerful tool to identify fluctuations between two types of hydrogen bond organizations in water molecules arranged around the surface of Brownian nanoparticles. The obtained results reveal that, in addition to identifying low and high-density liquid domains, the delicate balance between the coexistence of these different water domains is strongly influenced by the size of the nanoparticles and the pH of the aqueous medium, respectively corresponding to variations in temperature and pressure in a newly proposed hypothetical phase diagram of water.